2018
DOI: 10.1111/plb.12836
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the range of the medicinal herb Eriocaulon buergerianum Körnicke. (Eriocaulaceae) under climate change

Abstract: Eriocaulon buergerianum Körnicke. (Eriocaulaceae) is one of the most common and least expensive herbal medicines for eye disease. This species is facing potential threats from climate change. Insufficient biogeographic knowledge of this plant species can hinder its effective management for long-term population survival. We integrated ecological niche modelling (Biomod2) with 70 records of E. buergerianum and eight environmental variables to estimate changes in distribution over time. A core area Zonation algor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…According to previous studies, high suitable habitat of some species would shrink, even disappear, others would increase, and still others would remain stable in the future. Kurpis (Kurpis, Serrato-Cruz, & Feria Arroyo, 2019), Zhao(Zhao et al, 2020 and Xie(Xie et al, 2018) found the potential distribution of Tagetes lucida Cav. (Asteraceae), Notopterygium incisum Ting ex H. T. Chang (Apiaceae) and Eriocaulon buergerianum Kornicke.…”
Section: Shift Of Suitable Habitat In Futurementioning
confidence: 99%
“…According to previous studies, high suitable habitat of some species would shrink, even disappear, others would increase, and still others would remain stable in the future. Kurpis (Kurpis, Serrato-Cruz, & Feria Arroyo, 2019), Zhao(Zhao et al, 2020 and Xie(Xie et al, 2018) found the potential distribution of Tagetes lucida Cav. (Asteraceae), Notopterygium incisum Ting ex H. T. Chang (Apiaceae) and Eriocaulon buergerianum Kornicke.…”
Section: Shift Of Suitable Habitat In Futurementioning
confidence: 99%